Profiting with Values: A Qualitative Approach to SMEs in the Informal Economy of Uganda’s Central Region - Kintu, Ismail; Kiwala, Yusuf; Buyinza, Faizo (International Journal of Business and Management, 2020)
The study sought to establish the core values which influence SME profitability in Uganda’s informal economy. By employing a qualitative approach, interviews from twenty-five respondents were conducted. Data were analyzed by coding and networks with the help of the Atlas.ti 8 tool. The study findings indicate that: whereas the accounting profession defines profitability to be return on assets (ROA), return on investment (ROI), and return on equity (ROE), entrepreneurs in Uganda’s informal economy do not understand these traditional profit measurement criteria. Instead, they understand sales and expenses. Besides, fairness, respect, responsibility, and cleanliness were established as core values that catalyze SME sales. It is important for the government through the private-sector foundation and traders’ association to continuously train these entrepreneurs about financial matters. Also, the accounting professionals through the regulatory body may establish a wing that can help these informal traders in financial matters, the way the Uganda law society is approaching to help out vulnerable people who cannot afford the services of expensive lawyers.
Keywords: profitability, core values, informal economy, SMEs and qualitative